Alternative Extraction and Purification Methods of Gamma Oryzanol from Rice Bran and Its Antioxidant Scavenging Activity - Ruen-ngam, Duangkamol; Tawai, Chitti; Sukonthamut, Sujitra; Nokkoul, Raumjit (Journal of Food Technology, Siam University, 2018)
Oryzanols are well-known antioxidant and now used as food supplements. Crude rice bran oil (CRBO) composes of many impurities such as wax and gum sludge which are required to be removed prior to purifying CRBO with many serial steps. Firstly, CRBO was extracted from jasmine rice bran by cold press extraction and maceration with ethanol and hexane extraction then impurities; such as waxes and gums, were removed from the CRBO by 2 different systems, i.e., methanol:acetone and ethanol:acetone crystallisation systems which were then compared. The crystallisation involved two steps and yielded a solid and a liquid phase under cold conditions. The g-oryzanol content in all phases was analysed by RP-HPLC and the antioxidant scavenging activity was analyzed by DPPH assay. The g-oryzanol obtained from all conditions was a fine white to pale yellow crystal. The best extraction conditions were cold pressed extraction with crystallisation in ethanol: acetone, which yielded 12.31% g-oryzanol crystals with 94.71 % purity. The g-oryzanol crystals were evaluated for their antioxidant scavenging activity and had an IC50 of 0.171 mg/ml, with almost the same range as the BHT standard. However, it was lower than that obtained with a commercial g-oryzanol standard.